2007
DOI: 10.1507/endocrj.k06-147
|View full text |Cite
|
Sign up to set email alerts
|

Long-term Follow-up of Patients with Multiple Endocrine Neoplasia Type 1

Abstract: Abstract. Whether early surgical treatment of non-functioning pancreas islet cell tumor (NFPT) provides a favorable quality of life and life expectancy in patients with multiple endocrine neoplasia type 1 (MEN1) remains controversial. We analyzed the long-term clinical courses and surgical outcomes of 14 Japanese patients with MEN1-associated NFPTs. NFPTs smaller than 20 mm in diameter did not show any apparent growth over a long monitoring period. Furthermore, these small NFPTs did not metastasize to regional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(33 citation statements)
references
References 38 publications
0
32
0
1
Order By: Relevance
“…One has to keep in mind that with endoscopic ultrasound, more small NF-pNETs are currently diagnosed. They are usually indolent and demonstrate slow growth, with a doubling time of 5-10 years (Kann et al 2006, Sakurai et al 2007. When 46 patients with NF-pNETs !2 cm without surgical treatment were followed over 10 years, 17% showed increase in size, 11% developed a functional syndrome, 65% displayed stable disease, 2% died due to metastatic NF-pNETs, 2% due to other causes, and 2% was lost to follow-up (Triponez F, Goudet P, AFCE, & GTE unpublished observations presented at ENETS 2013, Barcelona, Spain).…”
Section: Epidemiologymentioning
confidence: 99%
“…One has to keep in mind that with endoscopic ultrasound, more small NF-pNETs are currently diagnosed. They are usually indolent and demonstrate slow growth, with a doubling time of 5-10 years (Kann et al 2006, Sakurai et al 2007. When 46 patients with NF-pNETs !2 cm without surgical treatment were followed over 10 years, 17% showed increase in size, 11% developed a functional syndrome, 65% displayed stable disease, 2% died due to metastatic NF-pNETs, 2% due to other causes, and 2% was lost to follow-up (Triponez F, Goudet P, AFCE, & GTE unpublished observations presented at ENETS 2013, Barcelona, Spain).…”
Section: Epidemiologymentioning
confidence: 99%
“…Most cohorts report that thymic NET occur predominantly in men with a mean age around the fifth decade (Teh et al 1997, Gibril et al 2003, Ferolla et al 2005, Sakurai et al 2007, Habbe et al 2008, Goudet et al 2009, de Laat et al 2014 in contrast with previous studies, a Japanese study reported a relatively high percentage (36%) of women in their cohort of MEN1 patients with a thymic NET (Sakurai et al 2013).…”
Section: Thymic Neuroendocrine Tumorsmentioning
confidence: 74%
“…While there is consensus that all NFPNETs larger than 2 cm or associated with symptoms (e.g., pain) should be resected due to the increased risk of malignancy and metastases, the optimal surgical approach for asymptomatic NF-PNETs less than 2 cm is less clear. 7,37,38 In patients with MEN-1, NF-PNETs are multifocal and according to autopsy series are present in 80% of patients with this syndrome. 7 Due to the multiplicity of tumors in these patients, local resection is not expected to result in a cure, and MEN-1 patients with NF-PNETs less than 2 cm have been found to have a survival of 100% at 15 years and rarely develop advanced disease.…”
Section: Nf-pnets Associated With Hereditary Syndromesmentioning
confidence: 99%